2018
DOI: 10.1158/1055-9965.epi-17-0855
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Screening Trends: Serial Cross-Sectional Analysis of the National Health Interview Survey Population, 2013–2015

Abstract: Rates of hepatitis C virus (HCV) infection are markedly higher for baby boomers compared with other birth cohorts, and they are now recommended for universal one-time screening. This study examines HCV screening rates and predictors for four birth cohorts [born <1945, born 1945-1965 (baby boomers), born 1966-1985, and born >1985] of a nationally representative sample over time. We used data from the 2013-2015 National Health Interview Surveys, an annual weighted survey of the U.S. civilian noninstitutionalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 32 publications
3
43
0
Order By: Relevance
“…Unlike HBV, there is no vaccine for HCV. Thus, the US CDC recommends all individuals in the Baby Boomer birth cohort should be screened for HCV, although only 12.8% of adults in this birth cohort have been screened . Most of the new cases of HCV are occurring in young, white injection drugs users living in rural areas.…”
Section: Infectious Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike HBV, there is no vaccine for HCV. Thus, the US CDC recommends all individuals in the Baby Boomer birth cohort should be screened for HCV, although only 12.8% of adults in this birth cohort have been screened . Most of the new cases of HCV are occurring in young, white injection drugs users living in rural areas.…”
Section: Infectious Agentsmentioning
confidence: 99%
“…Thus, the US CDC recommends all individuals in the Baby Boomer birth cohort should be screened for HCV, although only 12.8% of adults in this birth cohort have been screened. 160 Most of the new cases of HCV are occurring in young, white injection drugs users living in rural areas. Notably, HCV causes approximately 24.2% of liver cancers in the United States, and the incidence rate of hepatocellular carcinoma has tripled over the last decade, 157 in part because of an increased prevalence of chronic HCV infection.…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…However, our estimates are similar to national data that reported ~12% of baby boomers had been screened by the end of 2015. 10 Therefore, our results were unlikely to have been significantly affected by this limitation. Additionally, because this is a retrospective review of EMR data, our results are limited by physician recording and proper EMR documentation.…”
Section: Discussionmentioning
confidence: 82%
“…Patients in our study had similar percentages of HCV screening ordered as compared to self-reported national data reporting rates of HCV screening. 10 In both the EMR-verified and the self-reported national data, HCV screening was well below the CDC and USPSTF screening guidelines for universal screening of baby boomers. 7,9 Healthy People 2020 has a goal of increasing the number of people who are aware of their HCV infection from 53% to 60% 15 ; this is unlikely to happen without additional intervention.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation